TEORI MENEMPEL PADA SENI RUPA - Lina Marcelina; Desyandri; Farida Mayar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The sticking technique is a branch of fine arts which includes the activity of pasting pieces of paper or other materials to form a particular design or design. The purpose of this study is to explain the theory of sticking to fine arts. Various techniques are attached to elementary schools, namely collage, montage and mosaics. The method used to compile this article is a literature study. This literature review is a reference survey of books, articles. This article can be used as a reference for elementary school teachers in learning fine arts. Teachers are expected to be able to guide their students to learn the sticking process and it is hoped that students can explore themselves to create high creativity through sticking learning.